ANALISIS KINERJA PEGAWAI PADA SATUAN POLISI PAMONG PRAJA DI KABUPATEN BERAU - Warti Ratnasari; Irfan Abdullah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
The purpose of this research is to determine and analyze the extent to which the performance of employees at the Civil Service Police Unit in Berau Regency. The sample used in this study were 63 members of the Satpol PP of Berau Regency with simple random sampling technique (simple random method). Primary data is in the form of a questionnaire. The analytical tools used are: validity test, reliability test, and weighted factor value method.The results of this study conclude that the total value of the weighted factor for the performance of employees at the Civil Service Police Unit (Satpol PP) is 3.8 and is included in the criteria N> 3.Thus, the proposed research hypothesis is rejected, which means that the performance of employees in police units civil service in Berau Regency is good.The results of the respondent's assessment of the questionnaire distributed regarding the performance of employees at the Civil Service Police Unit in Berau District showed a positive response consisting of answers of